ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI HARGA SAHAM PADA PERUSAHAAN SUBSEKTOR FARMASI YANG TERDAFTAR DI BEI - Fathiy, Kamiliya; Aminda, Renea Shinta; Hurriyaturrohman, Hurriyaturohman (STIE Perbankan Indonesia, 2024)
The purpose of this writing is to determine the influence of fundamental factors, namely profitability and dividend policy and macroeconomics, namely gross domestic product (GDP) on share prices in pharmaceutical subsector companies listed on the Indonesia Stock Exchange for the 2017 - 2023 period. The research population is 13 pharmaceutical sub sector companies listed on the Indonesia Stock Exchange for the period 2017 – 2023. The sampling technique was purposive sampling and a sample of 5 companies was obtained. The data analysis technique used is panel data regression analysis with a significance level of 0.05. Based on the research results, it shows that partially profitability and dividend policy have a significant effect on share prices. Meanwhile, gross domestic product (GDP) has no significant effect on stock prices. Simultaneously, profitability, dividend policy and gross domestic product (GDP) have a significant effect on stock prices. Keywords: Profitability, Dividend Policy, Gross Domestic Product (GDP), and Stock Prices